The Influence of Educational Psychology on Modern Art Design Entrepreneurship Education in Colleges - Zhao, Huan; Li, Shuyi; Xu, Hui; Ye, Lele; Chen, Min (Frontiers in Psychology, 2022)
The purpose of this study is to analyze the relationship between psychology and modern art design education in colleges, and to provide the basis for improving the quality of art education in colleges. Based on the relevant theory, the characteristics of educational psychology and art psychology and the correlation between them were analyzed from the angle of art education. According to the characteristics of college students' psychological development, the significance of art psychology related courses was analyzed. Through the form of questionnaire, a total of 200 students (400 students in total) were randomly selected from Xi'an Academy of Fine Arts (professional art college) and Xi'an University of Science and Technology (comprehensive university), respectively. A total of 400 questionnaires were issued, and 382 valid questionnaires were recovered. The results show that almost all students in two colleges think pedagogy and educational psychology are the theoretical basis for art teachers, while less than one third of students in Xi'an University of Science and Technology think that art psychology is the theoretical basis for art teachers. The difference between the students' aesthetic and life values in the two colleges is significant (P<0.01). In the 15 directions of life values, there are significant differences in five directions: spirit - material (P<0.05), enrichment - emptiness (P<0.05), enthusiasm - apathy (P<0.05), hope - despair (P<0.01) and dedication - acceptance (P<0.01). It shows that the psychological and values of college students are changeable, and the educators should pay attention to the education in the related fields of psychology. This exploration was conducted based on educational psychology, which is of great significance for improving the educational level of art psychology in colleges and enable students to form correct aesthetic standards and life values.